The Role of Audit Committee in Evaluating Management Control: The Case of Ministry of Health, Poland - Dariusz KOTARSKI (Communications of International Proceedings, 2023)
The primary purpose of an audit committee is to provide information on the management control process and the internal audit process for their ministries, ensuring compliance with laws and regulations. The main objective of the article is to determine the role of the audit committee in the assessment of the functioning of the management control system in the Ministry of Health, with particular emphasis on organizational, legal and executive regulations. There were used analysis of documents of audit committee reports and the minister's statements on management control in years 2018-2022. Apart from that, in the paper, one can find an example of functioning of an audit committee and its objectives, tasks and the role in evaluating of management control in the Ministry of Health. The results show that between 2018 and 2022, all statements on the state of management control of the Ministry of Health were rated B, which means that adequate, effective and efficient management control functioned to a limited extent. On the contrary, the audit committee of the Minister of Health assumed that there is no need to signal material risks or weaknesses in management control. Selected objectives and measures of objective achievement in the management control of the Ministry of Health are discussed in the paper.
Keywords: audit committee; management control; internal audit.